On the Problem of Radar Monitoring of Ice Cover Formation and Destruction on Inland Waters: First Assessments - Karaev Vladimir; Sorokin Eugeny; Panfilova Mariya Andreevna; Titchenko Yuriy; Meshkov Evgeniy Mihaylovich; Kovaldov Dmitry (Russian Journal of Earth Sciences, 2025)
Remote sensing methods are widely used to monitor ongoing climate change, and the area of sea ice in the Arctic and Antarctic is used as one of the criteria. The duration of ice cover on inland waters can be used to assess processes within continents. The small size of internal waters does not allow the use of traditional methods that have proven themselves well in marine conditions. This study considers the possibility of using dual-frequency precipitation radar data to detect ice formation and destruction on small inland waters. Due to the features of backscatter at small incidence angles (< 18∘), inland waters with sizes smaller than the radar resolution (5 km) are “visible” in radar images. Using the Volga River as an example, it is shown that water-ice and ice-water transitions can be detected when analyzing radar images, and thus, possible to estimate the duration of ice cover on inland waters.